A new approach to predict the formation of 3D hybrid organic‐inorganic perovskites. Issue 22 (28th June 2019) - Kumar, Aditya; Singh, Ajeet; Ojha, Animesh K.
Abstract: Recently, hybrid organic‐inorganic perovskite (HOIPs) materials are used to enhance the power conversion efficiency of the solar cells. The tolerance factor (TF) and octahedral factor ( μ ) are widely used to predict the formation of three‐dimensional (3D) HOIPs structures. However, in some of the cases (e.g. CH3 NH3 GeI3 (MAGeI3 ) [TF = 1.06, μ = 0.33] NH2 CHNH2 GeI3 (FAGeI3 ) [TF = 1.14, μ = 0.33] and CH3 C(NH2 )2 GeI3 (ACGeI3 ) [TF = 1.17, μ = 0.33]), these factors could not predict the formation of HOIPs structures. Thus, we have introduced a new factor based on the HOMO‐LUMO energy gap of the organic cations, metal cations, anions, and volume of the organic cations. We have tested and utilized the HOMO‐LUMO energy gap factor ( β ) on 403 ABX3 combinations. The factor β successfully predicts and differentiate the perovskite and non‐perovskite materials. Further, we also observed that for the formation of HOIPs structure, volume of the organic cation should also be in the range of 20 to 46 cm 3 /mol. Based on the newly reported factor, we have also designed some new organic cations which may form a 3D HOIPs structure. Abstract : The HOMO‐LUMO energy gap of the perovskite fragments are used to designed a new factor for predicting the formation of perovskites and non‐perovskite. The newly designed factor nicely explained the nature of more than 99.5% of ABX3 combinations accurately. This factor can be applied on wide range of ABX3 combinations, with large number of variation of A site, variation of metal cation (Ca 2+, Sr 2+, Ba 2+, Mg 2+, Zn 2+, Mn 2+, Ge 2+, Pb 2+, Sn 2+ ) and X (Cl −, Br −, I −, [BF4 ] −, [BH4 ] − ).